HUBUNGAN KURANG ENERGI KRONIS (KEK) DENGAN KEJADIAN KETUBAN PECAH DINI (KPD) PADA IBU BERSALIN DI KLINIK NURHIKMAH GUBUG - Nurhikmah; Wahyu Utami Ekasari; Yuwanti (LPPM AN NUUR, 2024)
Background: Ongoing chronic energy deficiency in pregnancy, will interfere with the absorption of nutrients needed in the development of pregnancy will impact on the mother and fetus. Growth disorders resulting from conception, often occur immaturity, prematurity, premature rupture of membranes, congenital defects, or fetuses born with LBW.Methodology: This study used quantitative methods with a cross-sectional design. The sample in the study amounted to 212 respondents. Data analysis using the Chi-Square Test.Results: The results of statistical tests using the Chi-Square test obtained a p value of 0.000 which means that there is a relationship between Chronic Energy Deficiency in pregnancy with the incidence of premature rupture of membranes in laboring women at the Nurhikmah Gubug Clinic.Conclusion: There is a relationship between chronic energy deficiency in pregnancy and the incidence of premature rupture of membranes in laboring women at Nurhikmah Gubug Clinic.